Design of Automated Seed Sower with extended application using IoT - K., Priyadharshni; J., Mohana (International Journal of Psychosocial Rehabilitation, 2020)
Agriculture may be divided into several stages, such as seed sowing, seed germination, irrigation, etc. Our research is about the automation of some phases of farming. This study outlines the use of increased automation in the agricultural sector. It is recommended to have an automatic seed-sprowing robot controlled by a controller & wireless sensor network (WSN). Crops in the soil within a predefined distance are seeded using the automatic mechanism & controller. Post planting a seed in a series, the proposed robot automatically performs soil covering when it reaches the specified planting area. The seed planting machine could be operated via a phone or tablet, & this robot’s action can also be monitored remotely via a smartphone or computer.